Analysis of Social Emotional Development Through Together Eating Activities at NU Masyithoh Karanganyar Muslimat TPA 01 Dukuhturi Tegal District - Lukman, Saiful; Saroh, Lailis (Agrikan Jurnal Agribisnis Perikanan, 2024)
This article discusses social emotional development through eating together at TPA Muslimat NU Masyithoh Karanganyar 01 Dukuhturi, Tegal Regency. This research aims: To analyze the social emotional development experienced by children through group eating activities carried out at TPA Muslimat NU Masyithoh Karanganyar 01 Dukuhturi, Tegal Regency. The reality of this type of research is descriptive qualitative which describes the form of social emotional development experienced by children through group eating activities carried out at TPA Muslimat NU Masyithoh Karanganyar 01 Dukuhturi, Tegal Regency. Data collection techniques use observation, interviews and documentation methods. The data analysis techniques used are data reduction, data presentation, data validity and conclusion drawing. The results of this research show that at TPA Muslimat NU Masyithoh Karanganyar 01 Dukuhturi, Tegal Regency, children are able to develop social emotional skills. The better the child's social and emotional abilities, the more likely the child will be able to interact with the environment. Social Emotional Development includes: a) Social competence, namely establishing relationships with social groups; b) Social abilities, namely behavior used in social situations; c) Social cognition, namely understanding the understanding, goals and behavior of oneself and others; d) Prosocial behavior, namely the willingness to share, help, cooperate, feel comfortable and safe, and support others); d) Assignment of human values and morality, namely development in determining standards of good and bad).